Mengapa Relasi Suami-Isteri Tak Berimbang? - Najwah, Nurun (Sunan Kalijaga State Islamic University & The Asia Foundation, 2004)
Issues of husband-wife relationship are heatedly discussed in various events. This is based on the unfinished debate on the nature of husband-wife relationship: should the relations be based on senior-junior approach or on equal partnership? In this article, Nurun Najwah posts some reasons for the inequal positions of husband and wife in the family. She argues that this inequality is based on certain interpretations of some Qur'anic verses and hadith. Moreover, she offers an alternative solution in understanding husband-wife relationship.